Responding to the challenge of father absence and fatherlessness in the South African context: A case study involving concerned fathers from the North West Province - Freeks, Fazel (Stellenbosch Theological Journal, 2017)
This article is about the challenge of father absence and fatherlessness in the South African context, and the involving of concerned fathers. To address this challenge, an intervention was crucial as well as the training and equipping of fathers. This intervention consists of different fathers from the North West Province who responded to the challenge of father absence and fatherlessness after workshops presented in a narrative form. The workshops were based on research on fatherhood as this is conceptualized from a Biblical perspective. The research is necessary because South Africa experiences a challenge of absent fathers and fatherlessness. This research showed that the greatest problem with regard to fatherhood is centred on a man’s failure to resolve an identity crisis in the 21st century, but men are generally afraid to admit it. This problem has consequences for families and communities. Furthermore, this article reports on the responses and feedback of fathers and the supporting of literature in the research.